Comprehensive oxidation mechanisms of heterogeneous laminated HfB2–SiC/Ti ceramics under oxyacetylene conditions. Issue 7 (July 2022) - Bai, Yuhang; Wang, Peipei; Zhang, Baoxi; Du, Huiling; Cheng, Laifei
Abstract: A laminated HfB2 –SiC/Ti ceramic prepared via tape casting and spark plasma sintering was characterized upon an oxyacetylene torch test at 2040 ℃. The volatility diagram for the binary HfB2 –SiC system was established along with the detailed ablation microstructure of the upper surface to investigate the ablation behavior of the samples. In addition, the mass (8.93 mg/s) and linear ablation rate (1.22 µm/s) of the laminate are ascribed to the strong oxidation protection of the Ti interlayer by the dense SiO2 coating on the side surface, retarding the occurrence of oxidation weight loss and exfoliation at the interface. The corresponding oxidation behavior is proposed.